Phenotyping Cowpeas for Adaptation to Drought - Hall, Anthony (Frontiers in Physiology, 2012)
Methods for phenotyping cowpeas for adaptation to drought are reviewed. Key factors involve achieving optimal time of flowering and cycle length, and appropriate morphology for different types of cultivars as they relate to their utilization for dry grain, hay and fresh pea production. The strong resistance to vegetative-stage drought that is available, resistance to mid-season drought, escaping terminal drought, the delayed-leaf-senescence trait, water-use-efficiency, deeper rooting and heat tolerance are discussed. Diseases and pests that influence adaptation to drought are considered. Use of varietal intercrops and rotations are examined. Breeding and experimental field strategies for enhancing the adaptation to drought of cowpeas are described.